Dynamic Load Effects and Power Performance of an Integrated Wind–Wave Energy System Utilizing an Optimum Torus Wave Energy Converter - Wei Shi; Jinghui Li; Constantine Michailides; Mingsheng Chen; Shuaishuai Wang; Xin Li (Journal of Marine Science and Engineering, 2022)
To increase the utilization of wave and other renewable energy resources, an integrated system consisting of an offshore wind turbine and a wave energy converter (WEC) could be used to harvest the potential energy. In this study, a dimensionless optimization method is developed for shape optimization of a hollow cylindrical WEC, and an optimal shape is obtained using a differential evolution (DE) algorithm. The frequency domain response characteristics of the WEC with different geometric shapes and viscous damping loads are studied. The numerical model of the wind-wave integrated system, which consists of a semisubmersible platform and the WEC, is developed and used. The dynamic responses of the integrated system with and without using the WEC optimum section are compared. The results show that the dimensionless optimization method utilized in this paper is very applicable for hollow cylindrical WECs. A smaller inner radius and larger draft increase the heave RAO amplitude of the WEC significantly. In addition, optimization of the WEC shape and power take-off (PTO) damping coefficient can significantly improve the energy capture of the integrated system, which increases by 32.03%. The research results of this paper provide guidance for achieving the optimum design of offshore wind-wave energy integrated systems and quantify the benefits of using optimum designs in the produced wave energy power. In addition, the proposed dimensionless optimization method is generic and can be widely applied to different types of WECs.